Pencegahan dan Penanganan Penyakit Apendisitis pada Remaja di SMK PGRI 1 Cimahi - Theophylia Melisa Manumara; Wulan Nursifa; Dalfa Mutmainah; Abdurasyid Zakhir Syiham Yogaswara; Ayu Niasy; Gina Revana; Rianti Aprilia; Reiva Nur Ramadani; Damara Oktavia Aline; Indri Dwi Fitriani; Repa Wulandari; Nabila Agustin (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
Appendicitis is one of the most common abdominal emergencies among adolescents, with the potential to cause serious complications such as perforation and peritonitis if not treated in a timely manner. Adolescents’ lack of understanding regarding risk factors, early symptoms, and the importance of a healthy lifestyle served as the primary basis for implementing this community service program. This community service activity was designed to increase the knowledge and awareness of students at SMK PGRI 1 Cimahi regarding the prevention and early detection of appendicitis. The methodological approach included health education using presentation media, leaflets, and interactive discussions, accompanied by pre- and post-tests to evaluate changes in students’ understanding before and after the education. The material covered included the anatomy of the appendix, risk factors for appendicitis, clinical signs and symptoms, prevention through a high-fiber diet, and the need for prompt and accurate medical treatment. Evaluation results indicated a significant increase in students’ knowledge regarding the early detection of appendicitis and the maintenance of gastrointestinal health. Additionally, there was a positive shift in students’ attitudes toward healthy living behaviors and heightened awareness of acute abdominal pain symptoms. This program is expected to contribute as a promotive and preventive intervention in reducing the risk of appendicitis complications among adolescents, while simultaneously strengthening health literacy within the school community.